High Betaine and Dynamic Increase of Betaine Levels Are Both Associated With Poor Prognosis of Patients With Pulmonary Hypertension - Yang, Yicheng; Xu, Jing; Zhou, Jingjing; Xue, Jing; Gao, Jianing; Li, Xin; Sun, Bo; Yang, Beilan; Liu, Zhihong; Zhao, Zhihui; Luo, Qin; Zeng, Qixian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and objective: The association between plasma betaine levels and cardiovascular diseases have been revealed except for pulmonary hypertension (PH). In this study, we aimed to explore the role of betaine in patients with PH. Methods: Inpatients with PH at Fuwai Hospital were enrolled after excluding relative comorbidities. Each patient received at least one follow-up through clinical visit and the fasting blood was obtained both at the first and second hospitalization for betaine detection. Primary endpoint was defined as composite outcome events and the mean duration was 14.3 (6.9, 21.3) months. The associations of betaine and changes of betaine (Δbetaine) with disease severity and prognosis were explored. Results: Finally, in total of 216 patients with PH were included and the median for betaine plasma levels in total patients group, low betaine, and high betaine groups were 49.8 (39.0, 68.3)μM, 39.0 (33.5, 44.7)μM, and 68.1 (57.8, 88.7)μM respectively. High betaine was associated with poor WHO-FC, elevated NT-proBNP, low TAPSE and cardiac output index even after adjusting for confounders. Patients with high betaine were over twice risk to receive poor prognosis than those with low level [HR=2.080, (95%CI: 1.033-4.188)]. Moreover, the decrease of betaine level after further treatment was positively correlated to ΔNT-proBNP indicating Δbetaine might be an effector of disease severity, and dynamic increase of betaine was also associated with poor prognosis in PH. Conclusion: Betaine was associated with disease severity and might be an effector in PH. Patients with elevated level or with dynamic rise of betaine heralded a poor prognosis.